2012
DOI: 10.1021/ja305091n
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm for Reliable and General NMR Resonance Assignment

Abstract: The new FLYA automated resonance assignment algorithm determines NMR chemical shift assignments on the basis of peak lists from any combination of multidimensional through-bond or through-space NMR experiments for proteins. Backbone and side-chain assignments can be determined. All experimental data are used simultaneously, thereby exploiting optimally the redundancy present in the input peak lists and circumventing potential pitfalls of assignment strategies in which results obtained in a given step remain fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
255
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 175 publications
(263 citation statements)
references
References 37 publications
7
255
1
Order By: Relevance
“…Solid-state FLYA calculations (Schmidt et al 2013;Schmidt and Güntert 2012) were performed with CYANA version 3.97. The tolerance value for chemical shift matching was set to 0.55 ppm for 13 C and 15 N. The calculations are based on experimental peak lists as obtained from the manual assignment procedure.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 99%
“…Solid-state FLYA calculations (Schmidt et al 2013;Schmidt and Güntert 2012) were performed with CYANA version 3.97. The tolerance value for chemical shift matching was set to 0.55 ppm for 13 C and 15 N. The calculations are based on experimental peak lists as obtained from the manual assignment procedure.…”
Section: Solid-state Nmr Spectroscopymentioning
confidence: 99%
“…Owing to the current state of computational power, several studies have reported that fully automatic structure calculations from processed NMR data were feasible without any manual interpretation. [2][3][4][5] However, the improvements and refinements of NMR structures are still believed to be largely dependent on the skills and experiences of the researchers interpreting and calculating the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic algorithm [37], [38], [39] approaches are related to Monte Carlo methods and try to identify the optimal resonance assignments through evolution of set of initial random individual solutions. The optimal solution is deduced through multiple cycles of mutation and recombination.…”
Section: Tools For Automated Assignment Of Solution-state Nmr Datamentioning
confidence: 99%
“…This approach was developed on the basis of FLYA algorithm for automated assignment of solutionstate NMR peak lists within same CYANA software [39]. The ssFLYA algorithm is able to handle more standard 2D and 3D solid-state NMR peak lists such as 3D NCACB, 3D…”
Section: Tools For Automated Assignment Of Solid-state Nmr Datamentioning
confidence: 99%
See 1 more Smart Citation